Removal of Ozone by Urban and Peri‐Urban Forests: Evidence from Laboratory, Field, and Modeling Approaches. Issue 1 (1st January 2016) - Calfapietra, Carlo; Morani, Arianna; Sgrigna, Gregorio; Di Giovanni, Sara; Muzzini, Valerio; Pallozzi, Emanuele; Guidolotti, Gabriele; Nowak, David; Fares, Silvano
Abstract : A crucial issue in urban environments is the interaction between urban trees and atmospheric pollution, particularly ozone (O3 ). Ozone represents one of the most harmful pollutants in urban and peri‐urban environments, especially in warm climates. Besides the large interest in reducing anthropogenic and biogenic precursors of O3 emissions, there is growing scientific activity aimed at understanding O3 removal by vegetation, particularly trees. The intent of this paper is to provide the state of the art and suggestions to improve future studies of O3 fluxes and to discuss implications of O3 flux studies to maximize environmental services through the planning and management of urban forests. To evaluate and quantify the potential of O3 removal in urban and peri‐urban forests, we describe experimental approaches to measure O3 fluxes, distinguishing laboratory experiments, field measurements, and model estimates, including recent case studies. We discuss the strengths and weaknesses of the different approaches and conclude that the combination of the three levels of investigation is essential for estimating O3 removal by urban trees. We also comment on the implications of these findings for planning and management of urban forests, suggesting some key issues that should be considered to maximize O3 removal by urban and peri‐urban forests. Core Ideas: Urban and peri‐urban forests can contribute to O3 removal in cities. Combining different experimental approaches allows us to improve estimates of O3 fluxes. Choice of the right species and its physiological status can maximize O3 removal by vegetation.